How to talk with your kids about sex - Chirban, John T.; Andrews, Aurora, 1984- (Nashville : Thomas Nelson, 2012)
"Unfortunately, for many parents, the most important conversations are the hardest. Ninety-three percent of adults are dissatisfied with the sex education they received as children, which is precisely why they are so bad at teaching their kids-- they have no frame of reference. Renowned Harvard Medical School psychologist and frequent Dr. Phil guest John Chirban helps parents talk to their kids about sex. Kids are going to learn about sex, and it is up to parents to decide if their kids are going to learn from them or from MTV. How parents address sex-- their openness, the context, and their attitudes --will impact how their children view their own sexuality and self worth. Dr. Chirban helps parents know when, how, and how much. He uses humor, compassion, and real-life examples to prepare parents for a healthy and ongoing conversation that will equip their kids to own their own sexuality and an understanding of the larger issues of relationships, love, commitment, and intimacy. In addition, parents understand how helping their children understand these veiled yet critical keys of a fulfilling life deepens their own connection with their children."--Publisher's description.
Part I. Building the foundation: communicating effectively with your children about sex -- Part II. Time to talk: communicating with children at all ages and stages -- Part III. Getting down to the nitty gritty: issues, crises, and other complicated stuff.
"Help your children develop a positive, healthy attitude toward sex and relationships"-- Cover.
Includes bibliographical references (p. 281-284) and index.
Subtitle from cover.
Keywords: Sex instruction; Teenagers -- Sexual behavior; Sexual ethics; Parenting